THE EFFECT OF CERTAIN SYSTEMIC DISEASES ON THE OCCURENCE AND PROGRESSION OF GLAUCOMA - Bogdanova, Irina Lazarevska (Journal of Morphological Sciences, 2020)
Glaucoma is a progressive optic neuropathy, most commonly characterized by morphological changes in the papillae of the optic nerve and retinal nerve fibers, without the presence of other eye diseases or congenital anomalies. The risk factors for glaucoma can be divided into systemic and local. A case-control study was performed, which included patients aged 25 to 70. The study was conducted at the Clinic for Eye Diseases, in Skopje, in the Glaucoma Cabinet, in the period from 2015-2019.The study included 100 patients, who were divided into two groups. An exhaustive medical history was made about the involved patients. Regarding the systemic diseases in the patients included in our study, most of the patients 24.00% had increased blood pressure, 10.00% patients had heart disease, 5.00% patients had diabetes and the other category (10 different diseases) was registered in 10.00% patients. Due to a large standard error, the analysis excluded diabetes, high blood pressure and heart disease, and the category "others" was excluded because it contains various systemic diseases. It was found that patients who had heart disease 7.09 times had a slightly (p = 0.071) higher risk of glaucoma than patients who did not have systemic disease. Patients who had high blood pressure and diabetes by 1.97 times had a slightly higher risk (p = 0.439) of glaucoma than patients without systemic disease. The lowest predictive value for glaucoma prediction was registered in patients with increased blood pressure (0.93 times), insignificant (p = 0.883). Key words : systemic diseases, glaucoma, association